Using goats and sheep follicular fluid with LHRH-a and some dopamine antagonist in spawning of common carp(Cyprinus carpio) - S. AMEER, BAHA’A; I. SALIH, KHALIL; M. AL-RUBAEI, HASHIM (Journal of Kerbala for Agricultural Sciences, 2018)
The goats and sheep follicular fluid (FF), LHRH-a (Luteinizing hormone releasing hormone-analog), and some dopamine antagonists were used to stimulate common carp( cyprinus carpio) . The study included 24 females and 18 males and divided into 4 experiments. The results showed no significant differences between the females control group and the females treated in the first experiment, which used the FF for goats , motilium and a quarter of the amount of pituitary gland in its ratio and response time, total egg intake , quantity of eggs per kilogram of female and egg diameter with a reduction in injection cost 66.83%, while the males treatment were highly significantly ( P≤0.01) than males control of ratio and response time, total sperm volume, sperm volume per kilogram, and reduction in injection cost 87.64% .The results of the second experiment were significantly higher (P ≤0.05) than those of the control group on the treated females when the follicular fluid was used for goat, industrial hormone and metoclopramide, although the injection cost was reduced by 57%, while there were no significant differences between treatment and control males when used FF of goats and Metoclopramide with reduced injection cost of 88.21% . Also high significantly (P ≤0.01) female control group in the third experiment injected with pituitary extract on females treatment injected with follicular fluid for goat only .For the sheep follicle in the fourth experiment, the control females injected with the pituitary extract were significantly higher (P ≤0.01) than the females treated with follicular fluid for sheep, motilium and pituitary extract, while no significant difference was observed between males treated and control with reduced injection cost of 88.67% .